KUALITAS PELAYANAN TERHADAP LOYALITAS ANGGOTA PRODUK TABUNGAN UMUM SYARIAH - Alfiyanto (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
Service quality can be interpreted as an effort to fulfill customer needs and desires and the accuracy of their delivery in balancing customer expectations. Good and optimal service will have an impact on member loyalty to always consistently not switch to other financial institutions, members will always use their products or services and will later recommend them to others. The research method used is a quantitative approach. Data collection was carried out by filling out a research questionnaire given to 60 members of Islamic general savings products at KSPS BMT UGT Sidogiri Capem Banyuputih Situbondo. And the analysis technique used is the correlation coefficient (R), coefficient of determination, regression model, F test, and t test. Based on the results of the analysis in this study, it shows that service quality has a significant effect simultaneously on member loyalty. This is evidenced by the value of Fcount = 4.123> Ftable = 2.39 and the value of Sig. 0,003 ≤ 0,05. While the partially significant effect of service quality on member loyalty, as evidenced by the results of the reliability variable t test with a tcount value = 2.172> ttable = 2.000 and a Sig. value of 0.034 ≤ 0.05. 0,034 ≤ 0,05. And the empathy variable with a tcount value = 2.518> ttable = 2.000 and Sig value. 0,015 ≤ 0,05. Not all service quality sub-variables partially have a significant influence on the member loyalty variable. Physical evidence, responsiveness, and assurance variables partially have no significant effect on member loyalty. And of the five service quality sub variables that have the most dominant influence is the empathy variable with a regression coefficient value of 0.364.